Dieta e ecologia funcional da ema (Rhea americana) no Pantanal e Cerrado - Jacques, Cauê Lazareth Balassa (2024)
The rhea (Rhea americana) is the largest bird in South America, inhabiting, for example, the floodplains of the Pantanal and the savannas known as Cerrado in Brazil. In that study, the emu diet was evaluated in the Pantanal, revealing a variety of foods, with emphasis on leaves, fruits/seeds, invertebrates and small vertebrates. A diversity of plants consumed included legumes and species with fleshy fruits, such as Psidium sp. (Myrtaceae) and large palm seeds. This food variada suggests a potential role in seed dispersal, with the presence of apparently intact in feces. In a second stage carried out with emus in captivity revealed that they have a long gastrointestinal passage time, allowing the dispersal of seeds over long distances. The seeds ingested by R. americana presented variable results in germination, with some species benefited and others did not. The population decline of rheas could affect the regeneration of plants, especially when thinking about the quantitative component of the dispersal of seeds or dispersal distances. Understanding the ecological relationship between R. americana and native plants seems important for the dynamics and conservation of ecosystems where the species occurs.